Detection and analysis of new psittacine beak and feather disease virus (PBFDv) nucleotide sequences - VUCICEVIC, M; VUCICEVIC, I; DAVITKOV, D; DAVITKOV, D; STEVANOVIC, J; RESANOVIC, R; STANIMIROVIC, Z (Journal of the Hellenic Veterinary Medical Society, 2018)
Psittacine beak and feather disease (PBFD) affects a large number of Psittaciformes species. In this study, five White Cockatoo parrots (Cacatua alba) with clinical signs of PBFD were examined. After euthanasia, a full necropsy of parrots was performed and organs with macroscopic changes were sampled for routine histopathological evaluation. To confirm the presence of psittacine beak and feather disease virus (PBFDv), feather samples were analyzed with the PCR method. Sequence analysis of the obtained PCR products indicated their close relationship (99%) to other PBFDv isolates. Six variable nucleotide sites were discovered, two missense and four silent mutations. This paper presents the evidence of new PBFDv sequence in Cockatoo species.